2019
DOI: 10.1158/2326-6066.cir-18-0664
|View full text |Cite
|
Sign up to set email alerts
|

SLAMF6 as a Regulator of Exhausted CD8+ T Cells in Cancer

Abstract: The tumor microenvironment in leukemia and solid tumors induces a shift of activated CD8 + cytotoxic T cells to an exhausted state, characterized by loss of proliferative capacity and impaired immunologic synapse formation. Efficient strategies and targets need to be identified to overcome T-cell exhaustion and further improve overall responses in the clinic. Here, we took advantage of the E-TCL1 chronic lymphocytic leukemia (CLL) and B16 melanoma mouse models to assess the role of the homophilic cell surface… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…Our RNA-seq and ATAC-seq data revealed that Tox −/− P14 cells had a reduced expression of Slamf6 which was accompanied by massive changes in chromatin accessibility. Interestingly, SLAMF6 is an inhibitory receptor which is highly co-expressed with TCF-1 in the progenitor-like subset of exhausted CD8+ T cells in cancer 42 . We thus compared the expression of SLAMF6 and PD-1 in TCF-1 hi and TCF-1 lo subsets, respectively, in Tox +/+ and Tox −/− P14 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Our RNA-seq and ATAC-seq data revealed that Tox −/− P14 cells had a reduced expression of Slamf6 which was accompanied by massive changes in chromatin accessibility. Interestingly, SLAMF6 is an inhibitory receptor which is highly co-expressed with TCF-1 in the progenitor-like subset of exhausted CD8+ T cells in cancer 42 . We thus compared the expression of SLAMF6 and PD-1 in TCF-1 hi and TCF-1 lo subsets, respectively, in Tox +/+ and Tox −/− P14 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular staining of Tc cells showed that effector markers, lysosomal CD107a and granzyme B, and IL-2 expressing Tc cells were significantly increased in number. A lower percentage of CD8+PD-1+ TILs in anti-SLAMF6 injected mice were found compared to the control group, which suggests the activation of Tc’s in the tumor [ 130 ]. There is also a relation between the SLAMF6 gene and PDAC.…”
Section: Inhibitory Receptorsmentioning
confidence: 99%
“…The so called exhCD8 T cells progenitor population can be defined as PD-1 int (36) CXCR5 + (51) or Slamf6 + /Ly108 (38,52) lacking expression of TIM-3 ( 51), while terminally exhCD8 T cells are identified as PD-1 hi (36,37) or TIM-3 + (37, 51). Although several transcription factors have been proposed as key determinants of exhaustion programs, recent studies highlighted a dynamic interplay between T Cell Factor-1 (TCF-1) and thymocyte selection-associated high mobility group box protein (TOX), in the control of different exhausted populations (51,(53)(54)(55)(56).…”
Section: Cd8 T Cell Exhaustionmentioning
confidence: 99%